Epidemiology of non-odontogenic pain in UiTM Dental Centre: a retrospective study / Anis Zafirah Azman, Asilah Rahimi and Yoshinobu Shoji - Azman, Anis Zafirah; Rahimi, Asilah; Shoji, Yoshinobu (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Objective: The purpose of this retrospective study is to analyse the prevalence of patients referred to the Oral Medicine Clinic at UiTM Dental Centre that are diagnosed with non-odontogenic pain. This study is also done to classify the type of non-odontogenic pain that is most common to least commonly diagnosed while studying its correlation to age and gender. Methods: 200 patients referred to the Oral Medicine Clinic at UiTM Dental Centre and have been diagnosed by the specialist are selected. Their data including the diagnosis, age and gender are retrieved from the centre’s online dental records. Results: Among 109 patients, 72.5% are female while 27.5% are male. Most commonly diagnosed non-odontogenic orofacial pain is from musculoskeletal origin (83.1%), followed by neuropathic origin (6.8%), neurovascular (5.1%) and psychogenic (5.1%). Conclusion: Non-odontogenic pain mostly affected women compared to men, and the most common age to be affected is in the range of 21-30 years old. The most commonly diagnosed nonodontogenic pain is from musculoskeletal origin.